Extent to which instrumental / social networking will aid in job success - Lim, Joanna Jie Ying (2008)
Singapore’s service-related sector is growing and the race is on for employees to better themselves and bring their careers to greater heights. This research paper will help to further our understanding on the impact of networking and work performance on job success, and hopefully, provide some insights to our fellow countrymen as well.